Preparation method of multi-size single-crystal lithium manganese iron phosphate composite material and positive plate containing multi-size single-crystal lithium manganese iron phosphate composite material

Through the preparation of multi-size single-crystalline single-crystal lithium manganese iron phosphate composite materials, the problems of low conductivity and cycle performance attenuation of LMFP positive electrode materials are solved, high specific capacity and excellent cycle stability are achieved, suitable for large-scale production and reduce battery manufacturing costs.

CN119650651APending Publication Date: 2025-03-18YANCHENG INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411859884.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing lithium manganese iron phosphate (LMFP) cathode materials have problems with low intrinsic conductivity, poor magnification and low compaction density, and the Jahn-Teller effect leads to low battery capacity and attenuation of cycling performance.

Method used

The preparation method of multi-size single-crystalline manganese iron phosphate composite material is adopted. The preparation of lithium manganese iron phosphate precursor, graphitized carbon doping and amorphous carbon coating are used to control particle size and structure regulation to obtain a positive electrode material with high specific capacity and excellent cycle stability.

Benefits of technology

It achieves high specific capacity, excellent cycle stability and low production cost, and is suitable for large-scale production and improves the market competitiveness of batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650651A_ABST
    Figure CN119650651A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a multi-size single-crystal lithium manganese iron phosphate composite material and a positive plate containing the multi-size single-crystal lithium manganese iron phosphate composite material. The preparation method specifically comprises the following steps: S1, preparing a lithium manganese iron phosphate precursor; s2, preparing the nano-micro multi-size single crystal lithium manganese iron phosphate material doped with the graphitized carbon conductive material; s3, regulating and controlling the microstructure of the amorphous carbon coated multi-size single crystal composite lithium manganese iron phosphate material; and S4, preparing the composite lithium manganese iron phosphate material positive plate adopting the carbon-coated conductive foil. The invention relates to the technical field of lithium manganese iron phosphate materials of power batteries, the preparation method of the multi-size single crystal lithium manganese iron phosphate composite material is simple in overall steps, and square crystal particles are beneficial to improving the compaction density of the material and reducing side reaction active points on the surface of the material. By doping graphitized carbon and amorphous carbon coating and regulating and controlling a crystal structure, the electrical connection and synergistic effect among material particles are improved, material agglomeration is prevented, surface side reactions are reduced, gas production of a small-size particle material is inhibited, and the comprehensive electrical property of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a method for preparing a multi-sized single crystal lithium manganese iron phosphate composite material and a positive electrode sheet containing the same. Background Art

[0002] With the rapid development of battery-driven products such as electric vehicles and wearable devices, the demand for high-performance lithium-ion battery cathode materials is increasing. Lithium iron phosphate (LiFePO4, abbreviated as LFP) with an olivine structure has a stable structure during the charge and discharge process, and has good electrochemical properties, cycle performance and safety performance. It has broad application prospects in new energy vehicles and energy storage. However, its lithium insertion potential and intrinsic conductivity are low, the battery energy density usually does not exceed 200Wh / kg, and the low-temperature performance is poor. It cannot meet the growing applications with special requirements for high specific energy and low-temperature performance, which limits its further development. Through research, it was found that LiFePO4 is doped with a certain amount of Mn to generate lithium manganese iron phosphate (LiMn x Fe 1-x PO4, abbreviated as LMFP) is not only highly safe, but also Mn 3+ / Mn 2+ The working voltage is high (~4.1V), the theoretical energy density is 15%~20% higher than LiFePO4, and manganese resources are abundant. The cost of LMFP raw materials is only about 5-10% higher than that of LFP. Therefore, LMFP positive electrode materials have great application prospects in the fields of new energy vehicles and energy storage.

[0003] However, LMFP also has problems such as low intrinsic conductivity, rate difference and low compaction density. In addition, due to the presence of manganese, it is easy to cause the Jahn-Teller effect, especially when the manganese-iron ratio is too large, the Jahn-Teller effect is obvious, resulting in low battery capacity and rapid decay of cycle performance; when the manganese-iron ratio is too small, it cannot effectively improve the working voltage and battery specific energy.

[0004] At present, a large number of improved methods mainly include particle size nano-sizing, surface conductive carbon coating, metal cation doping, etc. At present, the main methods for preparing carbon coating that have been reported include sol-gel method, hydrothermal method, solid phase method, spray pyrolysis method, etc. Among the commonly used methods, the cost of raw materials used in sol-gel method is high and the production cycle is long; the conditions of hydrothermal method are difficult to control, the purity of the synthesized product is not high, and it is difficult to achieve large-scale production; compared with the above two methods, the solid phase method has the advantages of wide source of raw materials, low cost, high output, simple process, etc., but there are problems such as difficult to control the particle size of the material and uneven coating. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a multi-sized single-crystal lithium manganese iron phosphate composite material and a positive electrode sheet containing the same, so as to solve the problems raised in the above background technology.

[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing a multi-size single crystal lithium manganese iron phosphate composite material, comprising the following steps:

[0007] S1: Preparation of lithium iron manganese phosphate precursor: In a certain mass ratio of ethanol aqueous solution, the pH value is controlled at 10-12 by adding ammonia water, and soluble manganese salt, iron salt, phosphate and lithium salt are mixed according to LiMn x Fe 1-x The mixed solution prepared by the stoichiometric ratio in PO4 is slowly dripped into the ethanol aqueous solution, wherein the ratio of x is 0.3-0.7, and the lithium salt is in excess of 4-6% based on the stoichiometric ratio. During the dripping process, the pH value of the mixed solution is controlled within the range of 10-12 by adjusting the dripping speed. After the dripping is completed, stirring is continued for 2 hours. Then the above mixed solution is heated to 60°C and continued to stir to obtain a lithium manganese iron phosphate composite hydroxide precursor, and the precursor particle size is controlled by stirring or grinding to obtain a precursor mixture with multiple particle sizes;

[0008] S2: Add a particle size of 0.8-1.5um and a specific area of ​​5-12m to the lithium manganese iron phosphate precursor material obtained in step S1. 2 / g of phosphorus flake graphitized carbon is ground for 1 hour to control the particle size, and subjected to high temperature heat treatment at 300-500°C in an inert atmosphere for 4-6 hours.

[0009] S3: After the material obtained in S2 is cooled to room temperature under an inert atmosphere, a 2-5% by mass ratio of C6-C 10 The organic carbon source is heated to 500-750°C at a rate of 10-12°C / min under an inert atmosphere and calcined for 4-6 hours to control the particle size to obtain a uniform amorphous carbon-coated multi-size single crystal lithium manganese iron phosphate composite material;

[0010] As a further solution of the present invention: in step S1, the lithium salt is one of lithium carbonate and lithium hydroxide or a combination of the two, the manganese salt is one of manganese nitrate and manganese acetate or a combination of the two, the iron salt is one of ferrous nitrate and ferrous oxalate or a combination of the two, the phosphate is one of ammonium hydrogen phosphate and diammonium phosphate or a combination of the two, wherein the graphitized carbon is phosphorus flake graphite, and the amorphous carbon source is C6-C 10 Organic polyol carbon source.

[0011] A positive electrode sheet comprising a multi-sized single crystal lithium manganese iron phosphate composite material, the positive electrode sheet being manufactured by the following process:

[0012] S4: After the prepared multi-sized single-crystal lithium manganese iron phosphate composite material is crushed into nano-micron particle size, a certain amount of conductive agent and binder are added and mixed evenly, coated on the organic conductive carbon film conductive foil, dried at 80°C for 4 hours to remove moisture and volatile organic solvents, and a pressure of 20-30MPa is applied on a rolling mill. After maintaining for 5 minutes, a lithium manganese iron phosphate composite material positive electrode sheet is obtained.

[0013] Compared with the prior art, the present invention has the following beneficial effects: the preparation process is simple, easy to implement, and suitable for large-scale production; the obtained positive electrode materials of multiple particle sizes have high specific capacity and excellent cycle stability, and can achieve long-term charge and discharge cycles; the preparation cost is low, which can reduce the battery manufacturing cost and improve the market competitiveness of the battery.

[0014] At the same time, in the present invention, by doping graphitized carbon and amorphous carbon coating and regulating the crystal structure, the uniformity and conductivity of the surface coating of the lithium manganese iron phosphate material can be effectively improved, the electrical connection and synergistic effect between the material particles can be improved, the agglomeration of the material can be inhibited, the effective particle size distribution and compaction performance of the material can be improved, and the surface side reactions can be reduced to inhibit the gas production of small-sized particle materials. At the same time, manganese dissolution can be inhibited, thereby improving the use effect of the lithium manganese iron phosphate battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is the XRD pattern of the lithium iron manganese phosphate material obtained in Example 1 of the present invention;

[0016] Figure 2 This is a transmission electron microscope (TEM) image of the lithium manganese iron phosphate material obtained in Example 1 of the present invention;

[0017] Figure 3 0.2C charge-discharge curves of lithium manganese iron phosphate materials obtained in Example 1 of the present invention and Comparative Example 1;

[0018] Figure 4 0.1C, 0.5C and 1C charge-discharge curves of the lithium manganese iron phosphate material obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] The main equipment used in the following examples include: tubular resistance furnace, model OTF-1200X produced by Hefei Kejing Material Technology Co., Ltd.; planetary ball mill, model QM-3SP04 produced by Nanjing Nanda Instrument Co., Ltd.; constant temperature magnetic stirrer, model ZNCL-BS produced by Shanghai Yuezhong Instrument Equipment Co., Ltd.; blast drying oven, model DHG-9020SA produced by Shanghai Shunzhi Instrument Manufacturing Co., Ltd.; vacuum drying oven, model DZF-6050 produced by Hefei Kejing Material Technology Co., Ltd. Vacuum glove box, model Supper1220 produced by Mikaelona (Shanghai) Industrial Intelligent Technology Co., Ltd.; button battery sealing machine, model MSK-110 produced by Shenzhen Kejing Zhida Technology Co., Ltd.; battery testing system, model LAND-CT3002K produced by Wuhan Landian Electronics Co., Ltd.

[0021] Example 1

[0022] First, in an ethanol aqueous solution with a mass concentration of 50%, the pH value is controlled to 10-12 by dripping ammonia. At the same time, 39.17 grams of lithium carbonate (Li2CO3), 103.79 grams of manganese nitrate (Mn(NO3)2), 60.42 grams of ferrous oxalate (FeC2O4), and 132.06 grams of ammonium hydrogen phosphate ((NH4)2HPO4) (ratio 1.06:0.58:0.42:1) are dissolved in an ethanol aqueous solution with a mass concentration of 50%, and slowly added dropwise to the aforementioned solution. During the dropwise addition, the pH value of the mixed solution is controlled to be within the range of 10-12 by adjusting the dropping speed and stirring continuously. After the dropwise addition is completed, stirring is continued for 2 hours. Then a constant temperature magnetic stirrer is used to heat the above mixed solution to 60 degrees and continue stirring for 3 hours, and after filtering, a blast drying oven is used to dry to obtain a lithium manganese iron phosphate composite hydroxide precursor. Then, the precursor particle size is controlled by grinding with a planetary ball mill at a speed of 300 r / min, and a precursor mixture with multiple particle sizes of 500 nm-2 um is obtained by screening.

[0023] Add the lithium manganese iron phosphate precursor material obtained in the above step with a particle size of d50 of 0.8-1.5um and a specific area of ​​5-12m 2 / g of phosphorus flake graphitized carbon was ground in a planetary ball mill at 200r / min for 1 hour to control the particle size to 500nm-2um, and calcined at 500°C and 99.99% high-purity argon atmosphere for 6 hours to obtain lithium manganese iron phosphate material doped with graphitized carbon conductive agent.

[0024] After the lithium manganese iron phosphate material obtained above was cooled to room temperature in 99.99% high-purity argon, 9.10 grams of n-decanediol organic carbon source was added, and the temperature was raised to 750°C at a rate of 10°C / min for 6 hours in a 99.99% high-purity argon atmosphere. After cooling to room temperature in high-purity argon, a planetary ball mill was used to grind at 100r / min to control the particle size to 500nm-2um, and a multi-size single-crystal lithium manganese iron phosphate composite material with uniform amorphous carbon coating was obtained.

[0025] 20 grams of the lithium iron manganese phosphate composite material obtained in the above steps were added with 0.1 grams of carbon fiber as a conductive agent, 0.3 grams of PVDF as a binder, and 18 grams of N-methylpyrrolidone. After dissolving and stirring for 1.5 hours, the mixture was coated on a conductive aluminum foil (the carbon coating layer was 1-2 um), and dried in a vacuum drying oven for 4 hours to obtain a lithium iron manganese phosphate composite material positive electrode sheet.

[0026] Example 2

[0027] In a 50% mass concentration ethanol aqueous solution, the pH value is controlled at 10-12 by dripping ammonia water. At the same time, 24.91 grams of lithium hydroxide (LiOH), 125.97 grams of manganese acetate (Mn(CH3COO)2), 53.96 grams of ferrous nitrate (Fe(NO3)2), and 115 grams of diammonium phosphate (NH4H2PO4) (ratio 1.04:0.7:0.3:1) are dissolved in a 50% mass concentration ethanol aqueous solution, and slowly added dropwise to the aforementioned solution. During the dropwise addition process, the pH value of the mixed solution is controlled within the range of 10-12 by adjusting the dropwise addition speed and stirring continuously. After the dropwise addition is completed, stirring is continued for 2 hours. Then the above mixed solution is heated to 60°C using a constant temperature magnetic stirrer and continued to stir for 3 hours. After filtering, it is dried in a blast drying oven to obtain a manganese iron phosphate lithium composite hydroxide precursor. Then, the precursor particle size is controlled by grinding with a planetary ball mill at a speed of 300 r / min, and a precursor mixture with multiple particle sizes of 500 nm-2 um is obtained by screening.

[0028] Add the lithium manganese iron phosphate precursor material obtained in the above step with a particle size of d50 of 0.8-1.5um and a specific area of ​​5-12m 2 / g of phosphorus flake graphitized carbon was ground in a planetary ball mill at 200r / min for 1 hour to control the particle size to 500nm-2um, and calcined at 300°C and 99.99% high-purity argon atmosphere for 4 hours to obtain lithium manganese iron phosphate material doped with graphitized carbon conductive agent.

[0029] After the lithium manganese iron phosphate material obtained above was cooled to room temperature in 99.99% high-purity argon, 5.16 grams of hexanediol organic carbon source was added, and the temperature was raised to 500°C at a rate of 12°C / min for 6 hours in a 99.99% high-purity argon atmosphere. After cooling to room temperature in high-purity argon, a planetary ball mill was used to grind at 100r / min, and the particle size was controlled to be 500nm-2um, to obtain a multi-size single-crystal lithium manganese iron phosphate composite material coated with uniform amorphous carbon.

[0030] 20 grams of the lithium iron manganese phosphate composite material obtained in the above steps were added with 0.1 grams of carbon fiber as a conductive agent, 0.3 grams of PVDF as a binder, and 18 grams of N-methylpyrrolidone. After dissolving and stirring for 1.5 hours, the mixture was coated on a conductive aluminum foil (the carbon coating layer was 1-2 um), and dried in a vacuum drying oven for 4 hours to obtain a lithium iron manganese phosphate composite material positive electrode sheet.

[0031] Comparative Example 1

[0032] The difference between this comparative example and Example 1 is that the material particle size is not controlled to 500nm-2um during the entire preparation process, and no equal amount of phosphorus flake graphitized carbon and n-decanediol organic carbon source are added for coating, and other conditions and parameters are consistent with Example 1. The specific process is as follows:

[0033] In a 50% mass concentration ethanol aqueous solution, the pH value is controlled at 10-12 by dripping ammonia water. At the same time, 39.17 grams of lithium carbonate (Li2CO3), 103.79 grams of manganese nitrate (Mn(NO3)2), 60.42 grams of ferrous oxalate (FeC2O4), and 132.06 grams of ammonium hydrogen phosphate ((NH4)2HPO4) (ratio 1.06:0.58:0.42:1) are dissolved in a 50% mass concentration ethanol aqueous solution, and slowly added dropwise to the aforementioned solution. During the dropwise addition process, the pH value of the mixed solution is controlled within the range of 10-12 by adjusting the dropwise addition speed and stirring continuously. After the dropwise addition is completed, stirring is continued for 2 hours. Then the above mixed solution is heated to 60°C using a constant temperature magnetic stirrer and continued to stir for 3 hours. After filtering, it is dried in a blast drying oven to obtain a manganese iron phosphate lithium composite hydroxide precursor.

[0034] The lithium iron manganese phosphate precursor material obtained in the above steps was heated to 750° C. at a rate of 10° C. / min and calcined for 6 hours in a 99.99% high-purity argon atmosphere. After cooling to room temperature in the high-purity argon atmosphere, a lithium iron manganese phosphate composite material was obtained.

[0035] 20 grams of the lithium iron manganese phosphate composite material obtained in the above steps were added with 0.1 grams of carbon fiber as a conductive agent, 0.3 grams of PVDF as a binder, and 18 grams of N-methylpyrrolidone. After dissolving and stirring for 1.5 hours, the mixture was coated on a conductive aluminum foil (the carbon coating layer was 1-2 um), and dried in a vacuum drying oven for 4 hours to obtain a lithium iron manganese phosphate composite material positive electrode sheet.

[0036] Comparative Example 2

[0037] The difference between this comparative example and Example 2 is that the material particle size is not controlled to 500nm-2um during the entire preparation process, and no equal amount of phosphorus flake graphitized carbon and hexanediol organic carbon source are added for coating, and other conditions and parameters are consistent with Example 2. The specific process is as follows:

[0038] In a 50% mass concentration ethanol aqueous solution, the pH value is controlled at 10-12 by dripping ammonia water. At the same time, 24.91 grams of lithium hydroxide (LiOH), 125.97 grams of manganese acetate (Mn(CH3COO)2), 53.96 grams of ferrous nitrate (Fe(NO3)2), and 115 grams of diammonium phosphate (NH4H2PO4) (ratio 1.04:0.7:0.3:1) are dissolved in a 50% mass concentration ethanol aqueous solution, and slowly added dropwise to the aforementioned solution. During the dropwise addition process, the pH value of the mixed solution is controlled within the range of 10-12 by adjusting the dropwise addition speed and stirring continuously. After the dropwise addition is completed, stirring is continued for 2 hours. Then the above mixed solution is heated to 60°C using a constant temperature magnetic stirrer and continued to stir for 3 hours. After filtering, it is dried in a blast drying oven to obtain a manganese iron phosphate lithium composite hydroxide precursor.

[0039] The lithium iron manganese phosphate precursor material obtained in the above steps was heated to 500° C. at a rate of 10° C. / min and calcined for 6 hours in a 99.99% high-purity argon atmosphere. After cooling to room temperature in the high-purity argon atmosphere, a lithium iron manganese phosphate composite material was obtained.

[0040] 20 grams of the lithium iron manganese phosphate composite material obtained in the above steps were added with 0.1 grams of carbon fiber as a conductive agent, 0.3 grams of PVDF as a binder, and 18 grams of N-methylpyrrolidone. After dissolving and stirring for 1.5 hours, the mixture was coated on a conductive aluminum foil (the carbon coating layer was 1-2 um), and dried in a vacuum drying oven for 4 hours to obtain a lithium iron manganese phosphate composite material positive electrode sheet.

[0041] The positive electrode sheets obtained in the above Example 1, Example 2 and Comparative Example 1, Comparative Example 2 were punched out, and a metal lithium sheet was used as a counter electrode, a Celgard 2320 polypropylene film was used as a diaphragm, and 1.05 mol / L LiPF6 / (EC+DEC+DMC) (mass ratio 1:1:1) was used as an electrolyte. They were assembled in a high-purity argon glove box into CR2430 button batteries.

[0042] The electrochemical performance test of CR2430 button cell was carried out using the Blue Electric Battery Test System: (1) First charge and discharge capacity test: The battery was charged to 4.45V at a constant current and voltage of 0.05C, with a cut-off current of 0.01C. After standing for 5 minutes, it was discharged to 2.5V at 0.05C, and the discharge capacity and first charge and discharge efficiency of the battery were calculated; (2) 50 cycle performance test: The battery was charged to 4.45V at a constant current and voltage of 0.2C, with a cut-off current of 0.02C. After standing for 5 minutes, it was discharged to 2.5V at 0.2C, and the cycle was completed after 50 times, and the capacity retention rate was calculated; (3) Rate performance test: The battery was charged to 4.45V at a constant current and voltage of 0.1C, 0.2C, 0.5C, and 1C, respectively, with a cut-off current of 0.02C. After standing for 5 minutes, the battery was discharged to 2.5V using 0.1C, 0.2C, 0.5C, and 1C, respectively, and the rate discharge capacity of the battery was calculated. The test results are shown in Table 1 and Table 2:

[0043] Table 1. Charge and discharge performance test results

[0044]

[0045] Table 2. Rate performance test results

[0046]

[0047] In summary, in the embodiment of the present invention, controlling particle size, flaked graphitized carbon doping and amorphous carbon coating are one of the key steps of the multi-size single crystal lithium manganese iron phosphate composite material of the present invention. During the preparation process, the following issues need to be paid attention to in order to ensure the smooth progress of the preparation process and the quality of the final product:

[0048] Particle size control: The particle size of the lithium manganese iron phosphate precursor and the particle size of each subsequent intermediate material need to be strictly controlled, otherwise the final product may have too large crystal particles due to agglomeration during the roasting process. Since the olivine structure of the lithium manganese iron phosphate material leads to low intrinsic conductivity, reducing the particle size of the material is an effective way to improve the ion mobility of the material. However, the particle size cannot be too small, otherwise the specific surface area will be large, which will also lead to difficulties in material slurrying, low rolling density, and many side reactions. Therefore, it is necessary to accurately control the particle size of the intermediate product and the final product.

[0049] Exfoliated graphitized carbon doping and amorphous carbon coating: The olivine structure of lithium manganese iron phosphate material leads to low intrinsic conductivity of the material, so doping with conductive carbon and uniformly coating amorphous carbon during the preparation process can effectively improve the conductivity of the material, and can inhibit the increase and agglomeration of the particle size of the process products, reduce the side reactions of the material with the electrolyte, and improve the material capacity, rate capability and coulombic efficiency.

[0050] High-purity inert atmosphere control: Since the iron in lithium manganese iron phosphate needs to be ferrous to be active, the purity of the inert atmosphere needs to be strictly controlled to reach more than 99.99%, otherwise trivalent iron is easily generated.

[0051] It can be seen from the above embodiments that the method of the present invention can be adjusted according to specific needs to prepare multi-sized single-crystal lithium manganese iron phosphate composite materials suitable for different battery systems.

[0052] The embodiments of the present application are described above in conjunction with the accompanying drawings, but the present application is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the guidance of the present application, ordinary technicians in this field can also make many forms without departing from the purpose of the present application and the scope of protection of the claims, all of which are within the protection of the present application.

Claims

1. A method for preparing a multi-size single crystal lithium manganese iron phosphate composite material, characterized in that: The steps include: S1: Preparation of lithium iron manganese phosphate precursor: In a certain mass ratio ethanol aqueous solution, the pH value is controlled at 10-12 by dropping ammonia water, and at the same time, a mixed solution of soluble manganese salt, iron salt, phosphate and lithium salt prepared according to the stoichiometric ratio in LiMnxFe1-xPO4 is slowly dropped into the ethanol aqueous solution, wherein the ratio of x is 0.3-0.7, and the lithium salt is 4-6% in excess on the basis of the stoichiometric ratio; during the dropping process, the pH value of the mixed solution is controlled within the range of 10-12 by adjusting the dropping speed; after the dropping is completed, stirring is continued for 2 hours; then the above mixed solution is heated to 60°C and continued to be stirred to obtain a lithium iron manganese phosphate composite hydroxide precursor, and the precursor particle size is controlled by stirring or grinding to obtain a precursor mixture with multiple particle sizes; S2: Add a particle size of 0.8-1.5um and a specific area of ​​5-12m to the lithium manganese iron phosphate precursor material obtained in step S1. 2 / g of phosphorus flake graphitized carbon is ground for 1 hour to control the particle size, and subjected to high temperature heat treatment at 300-500°C in an inert atmosphere for 4-6 hours; S3: After the material obtained in S2 is cooled to room temperature under an inert atmosphere, a 2-5% by mass ratio of C6-C 10 The organic carbon source is heated to 500-750°C at a rate of 10-12°C / min under an inert atmosphere and calcined for 4-6 hours to control the particle size to obtain a uniform amorphous carbon-coated multi-size prismatic lithium manganese iron phosphate composite material.

2. The method for preparing a multi-size single crystal lithium manganese iron phosphate composite material according to claim 1, characterized in that: In step S1, the lithium salt is one of lithium carbonate and lithium hydroxide or a combination of the two, the manganese salt is one of manganese nitrate and manganese acetate or a combination of the two, the iron salt is one of ferrous nitrate and ferrous oxalate or a combination of the two, the phosphate is one of ammonium hydrogen phosphate and diammonium phosphate or a combination of the two, wherein the graphitized carbon is phosphorus flake graphite, and the amorphous carbon source is C6-C 10 Organic polyol carbon source.

3. A positive electrode sheet comprising a multi-sized single crystal lithium manganese iron phosphate composite material, characterized in that: The positive electrode sheet is made by the following process: S4: A multi-sized single-crystalline lithium iron manganese phosphate composite material is prepared according to the method for preparing a multi-sized single-crystalline lithium iron manganese phosphate composite material as described in any one of claims 1 to 3, and the multi-sized single-crystalline lithium iron manganese phosphate composite material is crushed into nano-micron particle size, and a certain amount of conductive agent and binder are added and mixed evenly, and coated on an organic conductive carbon film conductive foil, and dried at 80°C for 4 hours to remove moisture and volatile organic solvents, and a pressure of 20-30MPa is applied on a rolling mill and maintained for 5 minutes to obtain a lithium iron manganese phosphate composite material positive electrode sheet.